Tracking neurodegeneration in frontotemporal dementia and Alzheimer's disease: A comparative study of plasma tau and neurofilament light chain: Biomarkers (non‐neuroimaging): Blood based biomarkers. (7th December 2020) - Illán‐Gala, Ignacio; Lleó, Alberto; Karydas, Anna M.; Staffaroni, Adam M.; Zetterberg, Henrik; Sivasankaran, Rajeev; Grinberg, Lea Tenenholz; Spina, Salvatore; Kramer, Joel H.; Ramos, Eliana Marisa; Coppolla, Giovanni; Joie, Renaud; et al.
Abstract: Background: The comparative clinical utility of plasma Tau and neurofilament light chain (NfL) in frontotemporal lobar degeneration syndromes (FTLD‐S) and Alzheimer's disease (AD) was determined. Method: We measured plasma Tau and NfL with Simoa in 265 participants: 167 FTLD‐S, 43 AD and 55 healthy controls (HC), including 82 pathology‐proven cases (50 FTLD‐Tau, 18 FTLD‐TDP, 2 FTLD‐FUS and 12 AD) and 98 participants with amyloid PET. We compared cross‐sectional and longitudinal biomarker concentrations between groups, and studied their correlation with baseline clinical measures of disease severity and cortical thickness and their ability to predict disease progression and survival. Result: Plasma NfL, but not plasma Tau, discriminated between FTLD‐S, AD and HC (AUC = .97, 95% CI .95 – .99, p < .001 for FTLD‐S vs HC, and AUC = .94, 95 CI .89 ‐ .98, p < .001 for AD vs HC). In pathologically‐confirmed cases, plasma NfL levels were higher in FTLD‐TDP (85.6 ± 46 pg/mL), compared to FTLD‐Tau (50.4 ± 26 pg/mL), after accounting for age, and disease severity ( p < .001; partial η 2 = .20). High plasma NfL, but not plasma Tau, predicted disease progression in both FTLD‐S (2.3 points increase in CDRsb per log NfL ng/mL increase per time interval, 95% CI 0.4 – 4, FDR‐corrected, p =.007) and AD (2.9 points increase in CDRsb per log NfL ng/mL increase per time interval, 95% CI 0.2 – 5.6, FDR‐corrected, p = .035) and shorter survival (Log‐Rank = 14.4, p < .001) in FLTD‐S. Plasma NfL, but not plasma Tau, correlated with reduced cortical thickness in frontal regions in FLTD‐S and temporoparietal regions in AD. The combination of plasma NfL with plasma Tau did not improve the diagnostic prognostic performance of plasma NfL alone. Conclusion: Plasma Tau has limited diagnostic and prognostic value. Plasma NfL discriminates FTLD and AD from healthy individuals and is associated with disease progression in FTLD and AD and may be have important clinical value for prognostic purposes.